Biological programming - Ramsden, Jeremy J.; Bándi, Gergely (Collegium Basilea & AMSI, 2010)
Biology offers a tremendous set of concepts that are potentially very powerfully usable for the software engineer, but they have been barely exploited hitherto. In this position paper we propose a fresh attempt to create the building blocks of a programming technology that could be as successful as life. A key guiding principle is to develop and make use of unambiguous definitions of the essential features of life.